Economic Growth Mediates Village Funds And Original Local Government Revenue Towards Poverty In Regencies/Cities In East Java - Wibisono, Nurharibnu; Abidin, Munirul; Ekowati, Vivin Maharani (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Purpose: The mean of its research was to examine the effect of Village Funds and Local Government Revenue (PAD) on poverty mediated by economic growth in regencies and cities in East Java province.Design/Method/Approach: The research population is regencies/cities in East Java in 2015–2022. The data on Village Funds and Local Government Revenue were taken from the DJPK of the Ministry of Finance Republic Indonesia situs. The data on poverty and economic growth were obtained from the website of the Central Bureau of Statistics (BPS) of East Java Province. The data analysis used path analysis. Findings: The outputs declare Village Funds had a significant positive influence on poverty. Village Funds have no significant influence on economic accretion. Local Government Income has a significant negative influence on poverty. Local Government Revenue has a significant positive influence on economic accretion. Economic increases has a significant positive influence on poverty. Village Funds have a significant positive indirect impact on poverty by way of economic growth. Original Government Revenue has a significant positive indirect influence on poverty through economic increases.Originality/Values: Economic growth must be encouraged because it is able to mediates village funds and original local government revenue towards poverty in regencies/cities In East Java.